Significant Enhancement of Visible-Light-Driven Hydrogen Evolution by Structure Regulation of Carbon Nitrides - Han, Qing; Cheng, Zhihua; Wang, Bing; Zhang, Huimin; Qu, Liangti (ACS nano, 2018)
Photocatalytic water splitting for hydrogen evolution by utilizing solar energy has a great significance for high-density solar energy storage and environmental sustainability. Here, a defect-rich amorphous carbon nitride (DACN) photocatalyst has been synthesized by simply direct calcination of the rationally size-reduced urea crystals. The introduction of nitrogen vacancies combined with disordered structure cause a broad visible-light-reponsive range, countless lateral edge/exposed surface bonding sites, and quenched radiative recombination, suggesting that this DACN enhances photocatalytic activity for hydrogen production. A record high hydrogen evolution rate of 37,680 μmol h–1 g–1 under visible-light irradiation and an extraordinary apparent quantum efficiency of 34.4% at 400 nm were achieved, higher than most of the existing graphitic carbon nitride-based photocatalysts.